Radiation Exposure Characteristics among Healthcare Workers: Before and After Japan's Ordinance Revision - Imakhanova, Aiganym; Matsuda, Naoki; Takamura, Noboru; Oriuchi, Noboru; Ito, Hiroshi; Awai, Kazuo; Kudo, Takashi (Health physics (1958), 2024)
Radioactive materials and ionizing radiation have both medical value and disease risks, necessitating radiation dose measurement and risk reduction strategies. The International Commission on Radiological Protection (ICRP) lowered the lens of the eye exposure limit, leading to Japan's revised "Ionizing Radiation Ordinance." However, the effects on radiation exposure in medical settings and compliance feasibility remain unclear. To examine the impact of the revision to the "Ionizing Radiation Ordinance" and use it for measures to reduce exposure to radiation, a comprehensive analysis was conducted on data collected from Nagasaki University Hospital, Hiroshima University Hospital, and Fukushima Medical University Hospital in 2018, 2020, and April to September 2021. This included information on age, sex, occupation, department, and monthly radiation doses of workers, aiming to assess the impact of the revision to the "Ionizing Radiation Ordinance" on radiation exposure before and after its enforcement. Out of 9,076 cases studied, 7,963 (87.7%) had radiation doses below the measurable limit throughout the year. Only 292 cases (3.2%) exceeded 1 mSv y -1 , with 9 doctors and 2 radiological technologists surpassing 5 mSv y -1 . Radiological technologists showed significantly higher doses compared to doctors, dentists, and nurses (p < 0.01), while male subjects had significantly higher exposure doses than females (p < 0.01). No significant changes in radiation exposure were observed before and after the revision of the Ionizing Radiation Ordinance; however, variations in radiation exposure control were noted, particularly among nurses and radiological technologists, suggesting the impact of the revision and the need for tailored countermeasures to reduce radiation dose in each group.